Perancangan Sistem Promosi Produk Makanan Berbasis OpenChart Sebagai Media Pemasaran Digital Inovatif - Armando, M Yusuf; Annas, Firdaus; Arya Winaldi, Deni (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Digital transformation has provided significant opportunities for MSME (Micro, Small, and Medium Enterprises) entrepreneurs to utilize and leverage technology in expanding their visibility and product competitiveness. However, in Pariaman City, Padang Pariaman Regency still faces significant challenges in providing and maintaining adequate promotional media for MSME business owners, particularly for snack-related products. It is evident that the limited use of various digital platforms as effective promotional media hinders the development potential for broader marketing growth. This research was conducted to design an Opencart-based promotion system that can serve as a digital marketing medium to assist MSME entrepreneurs. The research methodology employed the R&D (Research and Development) approach with a development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The research resulted in a web-based digital platform specifically designed to address the gaps and needs of MSME players in Pariaman City. This research has undergone validation stages and has proven effective in improving product accessibility and availability in digital marketing. The findings confirm that Opencart is an excellent solution capable of meeting the digital promotion needs and addressing the shortcomings of MSMEs. Through this platform, MSME entrepreneurs can utilize technology for broader marketing reach, increased efficiency, and strengthened product competitiveness. The results of this research are expected to help encourage digital market innovation by MSME players and provide positive impacts on economic development in this digital era.